Association Between Perforating Scleral Vessel and Myopic Maculopathy: A Cross-Sectional Study of a Chinese Cohort - Yu, Huimin; Sun, Jinfu; Luo, Huan; Wang, Zhitao; Sun, Xufang (Frontiers in Medicine, 2022)
Purpose: To investigate the association between perforating scleral vessel (PSV) and different types of myopic maculopathy (MM) in a highly myopic population. Methods: In total, 188 highly myopic eyes (117 participants) were enrolled. Each participant underwent detailed history taking and ocular examinations. Based on fundus photographs and optical coherence tomography, patients were subdivided into the non-MM group and MM group. Based on a new classification system (ATN), MM cases were classified as myopic atrophy maculopathy (MAM), myopic tractional maculopathy (MTM), and myopic neovascular maculopathy (MNM). The number of PSV and the macular choroidal thickness (mChT) were measured. Results: Compared with non-MM group, MM group was characterized by relatively larger age (48.40 vs. 32.34; p < 0.001), longer axial length (AL, 29.72 vs. 27.75, p < 0.001), thinner mChT (52.90 vs. 122.52; p < 0.001), and lower PSV counts (6.73 vs. 9.47, p ≤ 0.001). The non-MM group had higher PSV counts in total area (0–9 mm, 9.47 vs. 6.73, p < 0.001) and perifovea area (3–9 mm, 7.25 vs. 4.71, p < 0.001) compared to the MM group. Univariate and multivariate analyses showed that PSV count had no association with MAM (p = 0.2419) and MTM (p = 0.5678). Total PSV count [odds ratio (OR) 0.78, 95% CI 0.64–0.95, p = 0.0149] and perifovea PSV count (OR 0.80, 95% CI 0.65–0.98, p = 0.0299) were both protective factors for MNM. The stratified analysis revealed that in groups with AL <28 mm, or mChT <50 μm, or mChT ≥100 μm, or eyes with cilioretinal artery, PSV count had no significant association with MNM. Conclusion: Higher PSV counts in perifovea area (3–9 mm centered fovea) and total area (0–9 mm centered fovea) were protective factors for MNM, whereas PSV count had no association with MAM and MTM. These findings may provide novel insights into the mechanisms of pathologic myopia.